Peningkatan Kepedulian Lingkungan Masyarakat melalui Gerakan Bersih Saluran Afvoer Kemambang - Samsul Arifin; Nur Vianti Lailatus Sifa; Didit Darmawan; Rafadi Khan Khayru; Fayola Issalillah (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
The waste problem in Indonesia remains a serious challenge that is difficult to overcome at all levels of society. Therefore, efforts to increase awareness and understanding of waste management need to be initiated early as a preventative measure to maintain environmental sustainability. This community service activity aims to raise environmental awareness through education on waste separation and management to ensure its usefulness. The method used was Participatory Action Research (PAR), which actively involved students, the community, and the East Java Environmental Agency (DLH) in every stage of the activity. The program was implemented in a planned manner, beginning with the opening, outreach, and clean-up of the Kemambang Afvoer canal. The results of the activity showed an increase in participants' understanding, particularly of the younger generation, of the importance of waste separation and management, especially plastic waste. Although some technical errors were encountered during the implementation, this activity encouraged the formation of early habits in adopting an environmentally friendly lifestyle. This early habituation is expected to contribute to improving the cleanliness and sustainability of the environment and rivers in the surrounding area.